Shadows and Silences in Göran Rosenberg’s Memoir: Jewish Postmemory in the Swedish Welfare State - Filipsson, Karin (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
This article, winner of the 2022 Marna Feldt Graduate Publication Award, explores the concept of postmemory in relation to Sweden’s cultural memory of World War II. Through an analysis of Göran Rosenberg’s memoir "Ett kort uppehåll på vägen från Auschwitz" (2012), translated as "A Brief Stop on the Road from Auschwitz," this article investigates how the representation of postmigrant identity and belonging relates to revisionist historiography regarding Sweden’s positionality during World War II. Furthermore, this article illuminates how exploring the postmemory trauma of the children of Holocaust survivors is relevant to the current discourse in Sweden’s contemporary transcultural society.